Free androgen index as a predictor of blood pressure progression and accelerated vascular aging in menopause - Georgiopoulos, G.A.; Lambrinoudaki, I.; Athanasouli, F.; Armeni, E.; Rizos, D.; Kazani, M.; Karamanou, M.; Manios, E.; Augoulea, A.; Stellos, K.; Papamichael, C.; Stamatelopoulos, K. (Atherosclerosis, 2016)
© 2016 Elsevier Ireland Ltd. Background and aims: We aimed to assess the prognostic value of free androgen index (FAI) and its change over time in arterial stiffness progression, endothelial function and hypertension in postmenopausal women. Methods: Postmenopausal women (n = 180) without clinically overt cardiovascular disease or diabetes were consecutively recruited and followed for a median of 29 months. The main outcome measures were changes over time in endothelial function (FMD), reflected waves, localized and systemic (PWV) arterial stiffness and hypertension. Results: Increased baseline FAI was significantly associated with new onset hypertension (OR for each SD, 2.71, 95% CI 1.14-6.41, p = 0.024), deterioration of pulse wave velocity (PWV) (0.414 m/s per SD), flow-mediated dilation (FMD) (-0.42% per SD), systolic (2.5 mmHg per SD) and pulse pressure progression (2.3 mmHg per SD, p < 0.05 for all). Baseline FAI remained an independent predictor of changes in PWV (p = 0.006), FMD (p = 0.02), peripheral pulse pressure (p = 0.028), transition to new onset hypertension (p = 0.001) and higher BP category (p = 0.012), after adjustment for age, changes in systolic blood pressure, traditional risk factors, vasoactive medication or total testosterone. Baseline FAI improved reclassification for the risk of transition into higher BP category (NRI = 47.5 ± 20.3%, p = 0.02) and abnormal PWV (NRI = 53.4 ± 23.2%, p = 0.021). Similarly, in a subgroup of patients with measured FAI at follow-up, its changes over time predicted changes in PWV, peripheral pulse pressure and hypertension status (p < 0.05 for all). Conclusions: In apparently healthy postmenopausal women, FAI could be a novel biomarker superior to total testosterone for accelerated vascular aging and hypertension status.
Keywords: Androgens; arterial stiffness; FAI; Hemodynamics; menopause